PENEGAKAN HUKUM PIDANA TERHADAP KASUS POLITIK UANG (MONEY POLITIC) DALAM PEMILIHAN UMUM ANGGOTA LEGISLATIF - Andri Herdiana; Imas Rosidawati Wiradirja (Iustitia Omnibus (Jurnal Ilmu Hukum), 2022)
ABSTRACT The 2019 direct legislative election system opened up the widespread practice of money politics in West Java Province, in a difficult situation like today, money is a powerful enough campaign tool to influence the public to vote for certain legislative candidates. The purpose of this study is to determine law enforcement against money politics cases that occur in the Legislative Member Election according to the electoral criminal justice system, and to analyze the factors that cause money politics and the efforts made in dealing with money politics cases in the Legislative Member Election. The research method uses a normative juridical research approach that examines and analyzes the law enforcement of money politics in the general election of legislative members. The results of this study found that the factors that cause money politics consist of habits (culture), low income levels (economics), and low public knowledge about politics. Efforts are being made in dealing with money politics cases in the Legislative Member Election by strengthening the integrity of election organizers and election supervisory institutions to minimize money politics practices. Keywords: Law Enforcement, Money politics, Bawaslu, Legislative Election, Election Criminal Court